Thinking (with) the body of Vitruvius' "Homo bene figuratus" - Winter, Kathrin (Ramus, 2023)
Vitruvius’ famous description of the homo bene figuratus possesses a slightly paradoxical nature. The description is meant to illuminate a fundamental but very abstract principle underlying the building of temples: symmetry or proportion. For the purpose of illumination, an analogy is drawn between temples and the human body. But even though the description serves an illustrative purpose, it does not at first sight appear to have a specifically illustrative nature since it largely consists of numerical fractions and proportional relations. Additionally, it seems quite difficult to tell what the homo bene figuratus actually looks like because the figure hardly possesses any individual features. And yet, the description inspired a rich reception of drawings during the Renaissance and later (of which Leonardo's version is certainly the most famous). The passage even seems to have taken on a life of its own since in those drawings the homo bene figuratus is usually treated independently of its original purpose and remains unconnected with temples or other buildings. Apparently, the passage—somehow—has an easily comprehensible or even perhaps vivid quality, despite the fact that it mainly lists abstract numerical details.
Published online by Cambridge University Press: 27 May 2024
Gesehen am 17.07.2024